The interplay of CSR, ethical leadership, and corporate governance on Indonesia’s construction material firm performance - Dewi, Theresia Dinda Kusuma; Ongkowijoyo, Gracia (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
This study examines how Corporate Social Responsibility (CSR), Ethical Leadership (EL), and Corporate Governance (CG) affect firm performance in Indonesia's construction materials industry. Using data from 84 industry professionals, the research employed partial least squares regression analysis to investigate these relationships. The findings reveal that corporate governance has a significant direct positive impact on firm performance, while CSR and ethical leadership show no significant direct effects. However, corporate governance plays a crucial moderating role, negatively moderating the relationship between CSR and performance while positively moderating the link between ethical leadership and performance. These results suggest that the effectiveness of both CSR initiatives and ethical leadership practices depends heavily on the strength of corporate governance mechanisms. The study contributes to stakeholder theory and provides practical insights for business leaders and policymakers on how to enhance organizational performance through better integration of social responsibility, ethical leadership, and governance practices. The findings highlight the importance of developing robust governance frameworks that can effectively translate CSR and ethical leadership initiatives into improved business outcomes.